LONG-TERM ATHLETIC DEVELOPMENT AS A FRAMEWORK TO INFLUENCE WELLNESS DURING CHILDHOOD AND ADOLESCENCE. (September 2020) - Eisenmann, Joey C.; Howard, Rick; Moreno, Tony
Abstract : Apply It!: Health and fitness professionals working with children and adolescents should first understand normal growth, maturation, and development (the "business of growing up") when considering the implementation and effect of lifestyle behaviors. Fundamental movement skills provide the foundation or building blocks for developing confidence and competency in sports, games, play, and physical activity and, along with developing muscular fitness, should be the focus of youth physical development. Along with physical activity, sleep and nutrition also serve as a polypill for optimal growth, maturation, and development. Youth programs should provide education and intervention on these key behaviors as well. Quality instruction and supervision of youth programs should include assessment and monitoring of growth and maturation, fundamental movement skill acquisition, physical performance, injury prevention, nutrition, sleep, and psychosocial well-being. Abstract : Today's youth face several challenges related to physical activity, sports, physical education, physical fitness, and psychosocial well-being. The long-term athletic development framework provides a blueprint for optimal health and well-being by engaging all youth regardless of ability or aspiration in programs that promote both physical fitness and psychosocial well-being.